The Influence of TikTok Shop Social Media Promotion on Consumer Purchase Decisions (A Case Study of Bestie Perfume Store in Luwu Regency) - M Fikram Al Hidayat; Jusri Jusri; Mulawarman Munsyir (Journal of Economics and Management Technologies, 2026)
This study aims to understand the influence of Promotion and TikTok Shop Social Media, both partially and simultaneously, on Consumer Purchase Decisions at Bestie Parfum Store, Luwu Regency. The research was conducted over a period of five (5) months, from March to July 2025. The type of research employed is quantitative. The population of this study includes all customers who have purchased perfume products at Bestie Parfum Store, with a total sales volume of 5,210 bottles. The sample size consists of 98 respondents, determined using the Slovin formula with a 10% margin of error. Data were collected through questionnaires and analyzed using reliability tests, validity tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of SPSS version 25. The findings of this study indicate that Promotion has a positive and significant partial influence on Consumer Purchase Decisions, with a t-value of 4.330 and a significance level of 0.000 < 0.05. Likewise, TikTok Shop Social Media also exerts a positive and significant partial influence on Consumer Purchase Decisions, with a t-value of 3.105 and a significance level of 0.003 < 0.05. Simultaneously, Promotion and TikTok Shop Social Media have a significant influence on Consumer Purchase Decisions, as indicated by an F-value of 26.799, which is greater than the F-table value of 3.09, at a significance level of 0.000 < 0.05.